Detailed Magnetic Force Analysis of A 4-Pole Hybrid Electromagnet by Magnetic Equivalent Circuit Method - Ertugrul, Hasan Fatih; Erkan, Kadir; Uvet, Huseyin (KOREAN MAGNETICS SOC, 2018)
In this paper, detailed magnetic force analysis of a 4-pole hybrid electromagnet system providing an advantage of full-redundant levitation is studied. The novel fragmented magnetic equivalent circuit method (MEC) is developed to accurately capture inherited nonlinear characteristics of 4-pole hybrid electromagnet to investigate force characteristics and magnetic field distribution. To confirm this method, two possible scenarios, which are levitation under plain core and levitation under dual-linear motor are composed. As well as, they are examined by both proposed method and FEM analyses. Comparative analyses of both methods revealed that force, inclination torque, and mutual interference can be easily captured with adequate accuracy while at the same time yielding less computation and set up time. Furthermore, the fragmented formulations of permeance functions can be generalized for the analysis and the design of similar devices which specifically involve inclination motions.
Keywords: 4-pole hybrid electromagnet; maglev; magnetic equivalent circuit method; magnetic force analysis; magnetic permanence modeling; 3D-FEM analysis; LEVITATION; Materials Science; Physics